Do people with private health insurance attach a higher value to health than those without insurance? Results from an EQ-5D-5 L valuation study in Ireland. Issue 6 (June 2020) - Hobbins, Anna P.; Barry, Luke; Kelleher, Dan; Shah, Koonal; Devlin, Nancy; Ramos Goni, Juan Manuel; O'Neill, Ciaran
Highlights: There is evidence of preference heterogeneity for health in Ireland related age, marital status and income. There is no compelling evidence that those with health insurance have different preferences for health to those without insurance in Ireland. Disparities in health and healthcare use in Ireland related to insurance are more likely to reflect disadvantage than differences in preferences. Abstract: Background: Differences in healthcare use could relate to differences in the values assigned health as well as to differences in access. We sought to establish whether there existed evidence of differences in values assigned health states between individuals with and without insurance in Ireland. Methods: Using the EuroQol Valuation Technology (EQ-VT), EQ-5D-5 L valuation tasks were administered to a sample of 1160 residents of Ireland in 2015/16. Censored panel regression analyses were used to estimate the values assigned health states. Private insurance was entered among a range of covariates to explain health preferences as a binary variable. A range of confirmatory analyses were undertaken. Results: In the primary analysis, possession of private health insurance was not a significant determinant of health preferences. Across a range of confirmatory analyses limited evidence of any difference in values related to health insurance emerged. Conclusions: Insurance status has been shown to be a significant determinant of healthcare utilization in Ireland after need has been controlled for. Our analysis provides no compelling evidence that meaningful differences exist in the values accorded health between those with and without health insurance.